Kodi Lee in Online Media: How is Autism Represented? - Catharina Griselda; Wawan Gunawan; Ruswan Dallyono (Passage, 2020)
This study entitled Kodi Lee in Online Media: How is Autism Represented? aims to reveal the representation of Kodi Lee, a savant autistic young man, in three different online media, namely Good Housekeeping US, The Wrap, and HuffPost. This study uses Halliday’s (1994) Systematic Functional Linguistic (SFL) focuses on Transitivity Analysis (TA) as the main analytical tool. Other theories uses to support the findings are representation (Hall, 1997), media representation (Orgad, 2012) and autism representation which includes savant autism (Prochnow, 2014) and mothering and autism (Stevenson, 2008). The findings show that material processes are dominantly used on the three websites. Material processes are used to describe Kodi’s talents. Meanwhile, from the analysis of verbal processes, it is evident that Kodi still cannot voice himself, even though he has some talents to be proud of, which on the same time contradicts with Clarke’s (2011) study. This study also finds that representations of Kodi are different on each media. Good Housekeeping US represents Kodi as a talented person with disabilities who stands behind his mother shadow. The Wrap represents Kodi as an extraordinary disabled young man who has a very strong bond with his mother, while HuffPost represents Kodi as a talented human being despite his disabilities. These results show despite Kodi’s claim as a savant autistic young man, the media still emphasize his disabilities to represent him. Keywords: autism, representation, savant autism, transitivity analysis